Iterative methods for solving space-time one dimensional multigroup diffusion equations. (22nd December 2009) - Yulianti, Y.; Su'ud, Z.; Waris, A.; Khotimah, S.N.
The numerical methods of Successive Overrelaxation (SOR), Successive-Line Overrelaxation (SLOR) and Alternating Direction Implicit (ADI) are used in this research to solve space-time one-dimensional diffusion equations. The results of this research have been compared with the ANL-Benchmark Problem BSS-6-A2. In general, the results are in agreement with the Argonne National Laboratory Benchmark Source Situation (BSS-6-A2). However, there is very little difference between SOR and ANL-BSS-6-A2 because of inner iterations in the SOR method. This research shows that the SLOR and ADI methods are more accurate and more efficient than the SOR method in solving space-time diffusion equations. SLOR is the most efficient in the case of a big number of mesh elements; however, the ADI method is the most efficient in the case of a small number of mesh elements.